Vaccine-Induced Immune Thrombotic Thrombocytopenia (VITT): Targeting Pathomechanisms with Bruton Tyrosine Kinase Inhibitors - von Hundelshausen, Philipp; Lorenz, Reinhard; Siess, Wolfgang; Weber, Christian (Thrombosis and Haemostasis, 2021)
A series of cases with rare thromboembolic incidents including cerebral sinus vein thrombosis (some of them fatal) and concomitant thrombocytopenia occurring shortly after vaccination with the coronavirus disease 2019 (COVID-19) vaccine AZD1222 (Vaxzevria) have caused significant concern and led to its temporary suspension in many countries. Immediate laboratory efforts in four of these patients have identified a tentative pathomechanism underlying this syndrome termed initially vaccine-induced prothrombotic immune thrombocytopenia (VIPIT) and renamed recently vaccine-induced immune thrombotic thrombocytopenia (VITT). It encompasses the presence of platelet-activating antibodies to platelet factor-4/heparin complexes, possibly emulated by polyanionic constituents of AZD1222, and thus resembles heparin-induced thrombocytopenia (HIT). Because these immune complexes bind and activate platelets via Fcγ receptor IIA (FcγRIIA), high-dose intravenous immunoglobulin G has been suggested for treatment of VITT in addition to non-heparin anticoagulants. Here we propose inhibitors of Bruton tyrosine kinase (Btk) approved for B cell malignancies (e.g., ibrutinib) as another therapeutic option in VITT, as they are expected to pleiotropically target multiple pathways downstream of FcγRIIA-mediated Btk activation, for example, as demonstrated for the effective inhibition of platelet aggregation, dense granule secretion, P-selectin expression and platelet-neutrophil aggregate formation stimulated by FcγRIIA cross-linking. Moreover, C-type lectin-like receptor CLEC-2- and GPIb-mediated platelet activation, the interactions and activation of monocytes and the release of neutrophil extracellular traps, as encountered in HIT, could be attenuated by Btk inhibitors. As a paradigm for emergency repurposing of approved drugs in COVID-19, off-label use of Btk inhibitors in a low-dose range not affecting haemostatic functions could thus be considered a sufficiently safe option to treat VITT.
Keywords: COVID-19 vaccine; thrombocytopenia; platelet; Btk; FcγRIIA